Impairment of Serotonergic Transmission by the Antiparkinsonian Drug L-DOPA: Mechanisms and Clinical Implications - Miguelez, Cristina; Benazzouz, Abdelhamid; Ugedo, Luisa; De Deurwaerdère, Philippe (Frontiers in Cellular Neuroscience, 2017)
The link between the anti-Parkinsonian drug L-3,4-dihydroxyphenylalanine (L-DOPA) and the serotonergic (5-HT) system has been long established and has received increased attention during the last decade. Most studies have focused on the fact that L-DOPA can be transformed into dopamine (DA) and released from 5-HT terminals, which is especially important for the management of L-DOPA-induced dyskinesia. In patients, treatment using L-DOPA also impacts 5-HT neurotransmission; however, few studies have investigated the mechanisms of this effect. The purpose of this review is to summarize the electrophysiological and neurochemical data concerning the effects of L-DOPA on 5-HT cell function. This review will argue that L-DOPA disrupts the link between the electrical activity of 5-HT neurons and 5-HT release as well as that between 5-HT release and extracellular 5-HT levels. These effects are caused by the actions of L-DOPA and DA in 5-HT neurons, which affect 5-HT neurotransmission from the biosynthesis of 5-HT to the impairment of the 5-HT transporter. The interaction between L-DOPA and 5-HT transmission is especially relevant in those Parkinson’s disease patients that suffer dyskinesia, comorbid anxiety or depression, since the efficacy of antidepressants or 5-HT compounds may be affected.